1983
DOI: 10.1021/ma00237a002
|View full text |Cite
|
Sign up to set email alerts
|

A computer model for the gel effect in free-radical polymerization

Abstract: In this paper the word enantioselective is always related to carbon 2 (enantiotopic) of the monomer, which becomes chiral after the insertion. The word diastereoselective is used with reference to the different reactivity of the diastereotopic faces of the monomer toward the insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
241
0
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(260 citation statements)
references
References 6 publications
13
241
0
6
Order By: Relevance
“…Como no caso anterior, estes fenômenos conduzem ao alargamento da distribuição de massas molares e afetam fortemente as propriedades finais dos polímeros [35,53,54] . O efeito vítreo aparece em polimerizações em que a temperatura de reação se encontra abaixo da temperatura de transição vítrea do polímero, em conversões superiores a 90%.…”
Section: Efeitos Gel E Vítreounclassified
“…Como no caso anterior, estes fenômenos conduzem ao alargamento da distribuição de massas molares e afetam fortemente as propriedades finais dos polímeros [35,53,54] . O efeito vítreo aparece em polimerizações em que a temperatura de reação se encontra abaixo da temperatura de transição vítrea do polímero, em conversões superiores a 90%.…”
Section: Efeitos Gel E Vítreounclassified
“…• The concentration of polymeric diradical species S n is three orders of magnitude smaller than the polymeric monoradicals P n and Q n [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. The diradical species S n could then be neglected [3,4,6,8,10] (Fig.…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…So, in order to account for the gel effect, a diffusion model taken from the literature and then modified by Table 4 Measured and predicted average molecular weights in number, measured average molecular weights in mass and optimized initiator efficiency Rouge [13] is taken. The expression proposed by Chiu [1] (for the methyl methacrylate) is the following:…”
Section: Gel Effect and Kinetic Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them are semi-empirical [1,8], others are based on parameters with clear physico-chemical meanings [2,7]. Several studies may be found in the literature on the comparison of different algorithms used for apparent rate constant calculation.…”
Section: Introductionmentioning
confidence: 99%